2020
DOI: 10.1007/s40615-020-00711-z
|View full text |Cite
|
Sign up to set email alerts
|

Poor Self-Rated Health Is Associated with Hospitalization and Emergency Department Visits in African American Older Adults with Diabetes

Abstract: Objectives We investigated the associations between poor self-rated health (SRH), hospitalization, and emergency department (ED) visits among African American older adults with diabetes mellitus (DM). Methods This survey recruited 235 non-institutionalized African American older adults (age > = 55 years) with diabetes mellitus (DM). Participants were recruited using a convenience sample from economically disadvantaged urban areas of South Los Angeles, California. Poor SRH was the independent variable. Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Consistent with prior research (Bennett et al, 2009;Y. J. Choi, 2020;Franks et al, 2003;Liang et al, 2010;Spencer et al, 2009;Yao & Robert, 2008), results indicated that SRH (Assari et al, 2020;Hastings, 2019). The health and well-being of Black adults is the result of intertwined relationships between individual, behavioral, social, and structural factors that have been endured across the life course (Bell et al, 2018;Thorpe Jr et al, 2015).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Consistent with prior research (Bennett et al, 2009;Y. J. Choi, 2020;Franks et al, 2003;Liang et al, 2010;Spencer et al, 2009;Yao & Robert, 2008), results indicated that SRH (Assari et al, 2020;Hastings, 2019). The health and well-being of Black adults is the result of intertwined relationships between individual, behavioral, social, and structural factors that have been endured across the life course (Bell et al, 2018;Thorpe Jr et al, 2015).…”
Section: Discussionsupporting
confidence: 76%
“…J. Choi, 2020; Franks et al, 2003; Liang et al, 2010; Spencer et al, 2009; Yao & Robert, 2008), results indicated that SRH was lower among Black older adults compared with Whites. This disparity is concerning, given that negative SRH is associated with increased risk of obesity, depressive symptoms, psychological distress, hospitalization, and emergency department visits among Black older adults (Assari et al, 2020; Hastings, 2019). The health and well-being of Black adults is the result of intertwined relationships between individual, behavioral, social, and structural factors that have been endured across the life course (Bell et al, 2018; Thorpe Jr et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults with diabetes endure many daily health management challenges surrounding their diet, blood glucose levels, medication and insulin injections, and skin and foot care [2][3][4][5][6]. Due to these challenges, older adults are more likely to experience acute and chronic complications related to their diabetes, which can subsequently lead to increased health care service utilization including hospitalization, emergency department (ED) visit, and mortality [7,8]. The total direct and indirect costs attributed to diabetes in the United States substantially increased from US $261 billion in 2012 to US $327 billion in 2017 [9].…”
Section: Introductionmentioning
confidence: 99%
“…The extended Whitelaw and Liang's 11 theoretical model proposed by Boehme, Geiser, & Renneberg explained that physical functioning reflects specific aspects of quality of life‐related to health where individuals are able to adapt to their environment 12 . Self‐rated health refers to individuals' perceptions of their current health and have been shown to be strong predictors of morbidity, hospitalization, and mortality 13–15 . Some studies have found that disability, diseases, and poor health status and perceptions of self‐rated health are risk factors for the occurrence of depression 5,16–19 …”
Section: Introductionmentioning
confidence: 99%